'Care' as camouflaging capitalism and obscuring harm: The user-generated pornography market and women's inequality. (March 2022) - McVey, Laura; Tyler, Meagan; Gurrieri, Lauren
Abstract: With the pornography industry's shift to platforms and a business model that heavily relies on user-generated content, there is a need to better understand how this industry sells itself to women as self-producing "content creators", especially considering the sexualised violence involved in marketing content to consumers. As one way to unpack some of the strategic underpinnings and market dynamics of this newer production model, we introduce an institutional logics approach to analyse materials from five pornography platform websites. We find the dominant integration of a theme of "care" is being sold to women; which both works to camouflage this market and its capitalist norms, while also functioning to obfuscate this market's harm. Our study is significant in mapping some of the more disguised, blurred and paradoxical practices of this user-generated market while also revealing the newer ways women's harm and inequality is being (re)produced in the selling of self-production.